Determinants of financial performance of general takaful and conventional insurance companies in Malaysia - Muhaizam Ismail (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2011)
Preserving financial stability is integral in developing financial institutions that are robust, resilient, effective and competitive. As such, this study examined factors that would affect the financial performance of the general takaful and conventional insurance companies in Malaysia. The main contribution of this study is that it is the first attempt to empirically investigate the determinants of the financial performance of general takaful and conventional insurance companies in Malaysia using a panel data set consisting of firm-specific data and economic data. In addition, this study pooled the data of the general takaful and conventional insurance companies to determine the overall perspective of the determinants of financial performance of the insurance industry in Malaysia. Two financial performance measures, which are investment yield and combined ratio, are used to capture the different aspects of the general takaful and conventional insurance operations in Malaysia. In analysing the determinants of the financial performance of the general takaful companies, the study examined the profit rate levels, equity returns of Shariah-compliant investments, size of company, retakaful dependence, solvency margin, liquidity, and contribution growth. In the case of conventional insurance, the factors examined in this study are interest rate levels, equity returns, size of company, reinsurance dependence, solvency margin, liquidity, and premium growth. The data covered a four-year period from January 2004 to October 2007. Three models of panel data estimation were employed, which are generalized least squares with non effects, generalized least squares with fixed effects and generalized least squares with random effects. These models were estimated for both performance measures. Based on the empirical results, this study found that size of company, retakaful dependence and solvency margin are statistically significant determinants of the investment performance of takaful companies. For conventional insurance, all factors are statistically significant determinants of investment performance, except for equity returns. In terms of underwriting performance, which is represented by the combined ratio, this study found that profit rate levels, equity returns, size of company, solvency margin and liquidity are significant determinants for the takaful sector. The findings for conventional insurance indicate that all factors are statistically significant determinants of the underwriting performance, with the exception of liquidity. The findings for the pooled data of the general takaful and conventional insurance companies are mostly consistent with the findings of the takaful and conventional insurance sectors.